Dermatitis artefacta in a patient with paranoid syndrome - Zalewska, Anna (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2007)
It is well recognized that psychosomatic factors play an important role in many skin diseases. Dermatitis artefacta coexists with quite an extensive number of psychopathologic conditions. In women, it is regarded as a "cry for help", especially when the patient is faced with psychosocial stressors. We present the case of a 40-year-old woman with long lasting self-inflicted excoriations and ulcerations of the skin located within easy reach of her hands. We discuss the reasons for such behavior and the possibilities of dermatological and general interventions.
Keywords: Avtodestruktivno vedenje; Dermatitis; dermatologija; Paranoid Disorders; Paranoja; Self-Injurious Behavior